PENYANDIAN FILE GAMBAR DENGAN METODE SUBSTITUSI DAN TRANSPOSISI SERTA IMPLEMENTASINYA MENGGUNAKAN BAHASA PEMROGRAMAN BORLAND DELPHI 7.0 - Dwi Retnosari (INFO-TEKNIK, 2013)
The study of how a message if safe so we can’t be read by unauthorized parties is cryptography. A message or information which is one important thing in communicating that needs to be kept confidential. For that need to be made an application that is able to secure information in general and particular image file. Cryptography has two of the encryption and decryption algorithms that allow massages can only be cre and read be the right. Method of the substitution and transposition is a conventional encryption techniques that can be used to source the information image file. In applications Borland Delphi programming language used to implement algorithms for encryption and decryption of substitution and transposition, resulting in the form of image files that cant not be read other without the decryption process first.